2023
DOI: 10.1002/alz.12942
|View full text |Cite
|
Sign up to set email alerts
|

A novel histological staging of hippocampal sclerosis that is evident in gray matter loss in vivo

Abstract: Introduction: Hippocampal sclerosis of aging (HS) is defined by end-stage histological findings, strongly associated with limbic-predominant age-related TAR DNA-binding protein 43 (TDP-43) encephalopathy (LATE). We aimed to characterize features of early HS to refine the understanding of its role within combined pathology. Methods:We studied 159 brain donations from the multimodal Vallecas Alzheimer's Center Study. A staging system (0 to IV) was developed to account for HS progression and analyzed in relation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 67 publications
3
14
0
1
Order By: Relevance
“…Conversely, other studies have highlighted the importance of HS in dementia [20,21], which allowed the observation of histological findings proposed as early HS [5,22]. In line with this work, we recently characterized early pathological changes of HS, proposing this pathology forms a wider spectrum than initially defined [23]. Following this re-classification, the prevalence of HS could have been underestimated in previous dementia studies, which reported a frequency of 3-30% following the classical definition [1,2,9].…”
Section: Introductionsupporting
confidence: 79%
See 4 more Smart Citations
“…Conversely, other studies have highlighted the importance of HS in dementia [20,21], which allowed the observation of histological findings proposed as early HS [5,22]. In line with this work, we recently characterized early pathological changes of HS, proposing this pathology forms a wider spectrum than initially defined [23]. Following this re-classification, the prevalence of HS could have been underestimated in previous dementia studies, which reported a frequency of 3-30% following the classical definition [1,2,9].…”
Section: Introductionsupporting
confidence: 79%
“…(A) HS groups defined as a function of HS staging including early and advanced stages (HS+ for those at stage>0) [23]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations